Monte Carlo simulation of Novalis Classic 6 MV accelerator using phase space generation in GATE/Geant4 code. (January 2019) - Teixeira, M.S.; Batista, D.V.S.; Braz, D.; da Rosa, L.A.R.
Abstract: GATE is a relatively new open source Monte Carlo software that was initially focused on PET and SPECT simulations. Since its 6.0 version that proposed new tools dedicated for radiation therapy simulations, GATE capabilities were extended for use in such kind of therapy. The Novalis 6 MV Classic was developed by partnership of Varian and Brainlab. This accelerator is a modified 6 MV LINAC from Varian's 600 C series that includes a Brainlab MLC (Multi-Leaf Collimator) system integrated into the LINAC head. In this work, the components of the LINAC, excepting the μMLC, were modeled using the GATE/Geant4 code version 7.1. The developed model was used in the validation of its 6 MV photon beam, applying the phase space technique. The phase space was used to store incoming particles before the secondary collimator and the information was stored as a ROOT file. The comparisons were performed with measurements in a water tank of 40 × 40 × 40 cm 3 at 100 cm Source to Surface Distance (SSD). The Percentage Depth Dose (PDD) and transverse profiles, at depth of 10 cm, for field sizes of 3 × 3 and 10 × 10 cm 2 (Novalis Classic maximum field size) were calculated using dosel sizes of 0.5 × 0.5 × 0.2 cm 3 and 0.2 × 0.5 × 0.5 cm 3 for PDD and profile measurements, respectively. It was observed that a proper mean electron beam energy of 5.8 MeV, sigma (standard deviation) of 0.174 MeV, and an electron spot size of 2 mm were the better parameters. The X-ray spectrum was determined and good agreements between simulation and measurements in water were observed, about 90% of checked points approved, considering a 3%/3 mm gamma index criterion, for square field sizes of 3 × 3 and 10 × 10 cm 2 . This work provided an investigation into GATE's capabilities in radiation therapy field and produced patient independent phase space files for the Novalis LINAC. Highlights: The components of NOVALIS 6 MV Classic were modeled using the GATE/Geant4. The simulated model was used in the validation of 6 MV photon beam, applying the phase space technique. The X-ray spectrum was determined with good agreements between simulation and measurements in water.